Nutritional and Sensory Characteristics of Catfish and Oyster Mushrooms Meatballs - Nuro, Jamilatun; Rosida, Dedin Finatsiyatull; Priyanto, Anugerah Dany (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Catfish is a type of aquaculture product that can be used to make meatballs. Catfish meat is white and has a savory taste. It is also nutritious. Using oyster mushrooms to make meatballs can increase their hardness because they contain pectin, which forms a colloidal dispersion in hot water and a chewy gel when cooled. Carrageenan is a gelling agent that increases the tenderness of catfish meatballs. This study aims to determine the effect of the proportion of catfish and oyster mushrooms on the nutritional value of catfish meatballs. The research employed a completely randomized design (CRD) factorial pattern, with factor I representing the proportion of catfish and oyster mushrooms (90:10, 80:20, and 70:30) and factor II representing the percentage of carrageenan added (1%, 2%, and 3%). The results of the study indicate that the optimal treatment involves a proportion of 80% catfish and 20% oyster mushrooms, along with the addition of 3% carrageenan, yielding a moisture content of 68.54%, ash content of 1.33%, protein content of 14.79%, fat content of 4.36%, carbohydrate content of 10.98%, and sensory value with appearance 8.08 (very like), aroma 7.96 (like), texture 7.79 (like), and taste 8.04 (very like). Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 12: Responsible Consumption and ProductionSDG 14: Life Below Water